Continuous Glucose Monitoring Systems: Applications and Integrated Benefits - review study - Goleniewska, Klaudia; Miasnikiewicz, Jakub; Ciechomski, Kamil; Cecuła, Wiktoria; Rypel-Bośka, Joanna; Siuta, Natalia; Stupecka, Aleksandra; Migiel, Marcin; Brynczka, Izabela (Quality in Sport, 2025)
Introduction: Continuous Glucose Monitoring (CGM) systems have evolved significantly, transforming the management of diabetes and expanding into various other fields. Originally developed to aid in diabetes management, CGM systems now offer real-time glucose tracking, providing insights into glycemic control, preventing hypoglycemia, and optimizing therapeutic decisions. These systems are used in type 1 and type 2 diabetes management, pregnancy, sports, and critical care. Despite their benefits, challenges such as cost and integration into routine care remain. Future research will be crucial to fully understand the long-term impact and cost-effectiveness of CGM systems. Aim of the study: This study aims to present the diverse applications and integrated benefits of Continuous Glucose Monitoring (CGM) systems. It focuses on their role in improving diabetes management, enhancing pregnancy outcomes, supporting athletic performance, and optimizing care in critical conditions. Materials and methods: A literature review was conducted using PubMed as the primary database. The search terms included: "continuous glucose monitoring", “CGM”, “diabetes mellitus", “diabetes mellitus type 1”, “diabetes mellitus type 2”. Conclusion: Continuous glucose monitoring (CGM) systems have significantly advanced diabetes care, offering precise, real-time glycemic data that support individualized treatment. This review highlights CGM’s broadening applications across diverse populations, including non-diabetic individuals, pregnant women, athletes, and critically ill patients. While strong evidence supports CGM’s clinical and behavioral benefits, further research is required to optimize cost-effectiveness, long-term outcomes, and broader implementation strategies. CGM represents a transformative tool in both chronic disease management and personalized health monitoring.